Vulture investors and the market for control of distressed firms - Hotchkiss, Edith S.; Mooradian, Robert M. (Journal of Financial Economics, 1997)
This paper investigates the role of vulture investors in the governance and reorganization of a sample of 288 firms that default on their public debt. The improvement in post-restructuring operating performance relative to the pre-default level is greater when the vulture investor becomes CEO or chairman or gains control of the target firm. We also find positive abnormal returns for the target's common stock and bonds in the two days surrounding the announcement of a vulture purchase of public debt or equity. Our evidence suggests that vulture investors add value by disciplining managers of distressed firms.